Tinjauan Hukum Perlindungan Konsumen Terhadap Transaksi Digital Pada Platform Online - Helga Putri Dahayu; Adbaida (GLOBAL SCIENTS PUBLISHER, 2025)
The advancement of information technology has significantly transformed consumer transaction patterns, shifting from conventional systems to digital platforms. Transactions conducted through e-commerce, marketplaces, and social media offer convenience but also pose new legal challenges such as online fraud, substandard products, and misuse of personal data. This study aims to evaluate the adequacy of Law Number 8 of 1999 on Consumer Protection (UUPK) in addressing the complexities of digital transactions. The research employs a normative juridical method using statutory and comparative approaches. The findings indicate that the UUPK has not yet fully accommodated the characteristics of digital transactions, particularly regarding electronic evidence, standard terms in online services, and consumer data protection. Compared to legal frameworks in other jurisdictions such as the European Union and Singapore, Indonesia's regulatory system still requires substantial reform to ensure effective and equitable consumer protection. Therefore, policy reform is urgently needed, either through the amendment of the UUPK or the formulation of a specific regulation (lex specialis) on digital consumer protection that is integrated with the Electronic Information and Transactions Law and the Personal Data Protection Law.